A Study to Determine if Addition of Palatal Petechiae to Centor Criteria Adds More Significance to Clinical Diagnosis of Acute Strep Pharyngitis in Children - Kumara V. Nibhanipudi MD, FAAP, FAAEM (SAGE Publishing, 2016)
Objective . A study to determine if addition of palatal petechiae to Centor criteria adds more value for clinical diagnosis of acute strep pharyngitis in children. Hypothesis . In children, Centor Criteria does not cover all the symptoms and signs of acute strep pharyngitis. We hypothesize that addition of palatal petechiae to Centor Criteria will increase the possibility of clinical diagnosis of group A streptococcal pharyngitis in children. Methods . One hundred patients with a complaint of sore throat were enrolled in the study. All the patients were examined clinically using the Centor Criteria. They were also examined for other signs and symptoms like petechial lesions over the palate, abdominal pain, and skin rash. All the patients were given rapid strep tests, and throat cultures were sent. No antibiotics were given until culture results were obtained. Results . The sample size was 100 patients. All 100 had fever, sore throat, and erythema of tonsils. Twenty of the 100 patients had tonsillar exudates, 85/100 had tender anterior cervical lymph nodes, and 86/100 had no cough. In total, 9 out of the 100 patients had positive throat cultures. We observed that petechiae over the palate, a very significant sign, is not included in the Centor Criteria. Palatal petechiae were present in 8 out of the 100 patients. Six out of these 8 with palatal petechiae had positive throat culture for strep (75%). Only 7 out of 20 with exudates had positive strep culture. Sixteen out of the 100 patients had rapid strep test positive. Those 84/100 who had negative rapid strep also had negative throat culture. Statistics . We used Fisher's exact test, comparing throat culture positive and negative versus presence of exudates and palatal hemorrhages with positive and negative throat cultures and the resultant P value <.0001. Conclusion . Our study concludes that addition of petechiae over the palate to Centor Criteria will increase the possibility of diagnosing acute group A streptococcal pharyngitis in children.